Highly purified fibroblast-derived growth factor, an SV40-transformed fibroblast-secreted mitogen, is closely related to platelet-derived growth factor. - Stroobant, P (1985)
Fibroblast-derived growth factor (FDGF), a polypeptide secreted by an SV40-transformed baby hamster kidney cell line (SV28), was purified approximately 1000-fold from SV28-conditioned medium. FDGF, which gave a single band on SDS-polyacrylamide gel electrophoresis, is a hydrophobic and cationic protein of apparent mol. wt. 31 000 containing disulphide-linked polypeptides. This factor is positive in Western blots using human platelet-derived growth factor (PDGF) anti-serum. FDGF is a potent mitogen for Swiss 3T3 cells; half-maximal stimulation of DNA synthesis was achieved at a concentration of approximately 1 nM, comparable with those for human and porcine PDGF. FDGF inhibits EGF binding to Swiss 3T3 cells, as does PDGF. The coincidence of the physical, biological and immunological characteristics of FDGF and PDGF strongly suggests that they are closely related in structure.